MED12 interacts with the heat‐shock transcription factor HSF1 and recruits CDK8 to promote the heat‐shock response in mammalian cells. Issue 14 (15th June 2021) - Srivastava, Pratibha; Takii, Ryosuke; Okada, Mariko; Fujimoto, Mitsuaki; Nakai, Akira
Abstract : Activated and promoter‐bound heat‐shock transcription factor 1 (HSF1) induces RNA polymerase II recruitment upon heat shock, and this is facilitated by the core Mediator in Drosophila and yeast. Another Mediator module, CDK8 kinase module (CKM), consisting of four subunits including MED12 and CDK8, plays a negative or positive role in the regulation of transcription; however, its involvement in HSF1‐mediated transcription remains unclear. We herein demonstrated that HSF1 interacted with MED12 and recruited MED12 and CDK8 to the HSP70 promoter during heat shock in mammalian cells. The kinase activity of CDK8 (and its paralog CDK19) promoted HSP70 expression partly by phosphorylating HSF1‐S326 and maintained proteostasis capacity. These results indicate an important role for CKM in the protection of cells against proteotoxic stress. Abstract :